Functional near-infrared spectroscopy-based correlates of prefrontal cortical dynamics during a cognitive-motor executive adaptation task - Gentili, Rodolphe J.; Shewokis, Patricia A.; Ayaz, Hasan; Contreras-Vidal, Jose L. (Frontiers in Human Neuroscience, 2013)
This study investigated changes in brain hemodynamics, as measured by functional near infrared spectroscopy, during performance of a cognitive-motor adaptation task. The adaptation task involved the learning of a novel visuomotor transformation (a 60° counterclockwise screen-cursor rotation), which required inhibition of a prepotent visuomotor response. A control group experienced a familiar transformation and thus, did not face any executive challenge. Analysis of the experimental group hemodynamic responses revealed that the performance enhancement was associated with a monotonic reduction in the oxygenation level in the prefrontal cortex. This finding confirms and extends functional magnetic resonance imaging and electroencephalography studies of visuomotor adaptation and learning. The changes in prefrontal brain activation suggest an initial recruitment of frontal executive functioning to inhibit prepotent visuomotor mappings followed by a progressive de-recruitment of the same prefrontal regions. The prefrontal hemodynamic changes observed in the experimental group translated into enhanced motor performance revealed by a reduction in movement time, movement extent, root mean square error and the directional error. These kinematic adaptations are consistent with the acquisition of an internal model of the novel visuomotor transformation. No comparable change was observed in the control group for either the hemodynamics or for the kinematics. This study (1) extends our understanding of the frontal executive processes from the cognitive to the cognitive-motor domain and (2) suggests that optical brain imaging can be employed to provide hemodynamic based-biomarkers to assess and monitor the level of adaptive cognitive-motor performance.